2017
DOI: 10.1007/s11356-017-9505-4
|View full text |Cite
|
Sign up to set email alerts
|

Domestic wastewater treatment by constructed wetlands enhanced with bioremediating rhizobacteria

Abstract: Constructed wetlands (CWs) offer several advantages for treating waters; however, the successful application of these systems remains a challenge. Practical solutions to pollution through CWs remain incipient because wetlands are still studied as "black boxes"; further studies are required regarding the involvement of rhizosphere bacteria in the removal of pollutants. This research focused on increasing the performance of CWs treatment systems for the removal of inorganic and organic pollutants from domestic w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…53 As shown in Figure 5E, MDA increased in the 1000 μg/L treatment group, which is a hidden danger to photosynthetic ability. Racchetti et al 54 and Salgado et al 55 proved that when leaves' photosynthetic ability was destroyed, oxygen and organic matter cannot be successfully produced and transferred to the rhizosphere, which resulted in attenuated nitrification and denitrification in rhizospheres, thereby reducing nitrogen process.…”
Section: Nanoplastics Disrupt Microbialmentioning
confidence: 99%
“…53 As shown in Figure 5E, MDA increased in the 1000 μg/L treatment group, which is a hidden danger to photosynthetic ability. Racchetti et al 54 and Salgado et al 55 proved that when leaves' photosynthetic ability was destroyed, oxygen and organic matter cannot be successfully produced and transferred to the rhizosphere, which resulted in attenuated nitrification and denitrification in rhizospheres, thereby reducing nitrogen process.…”
Section: Nanoplastics Disrupt Microbialmentioning
confidence: 99%
“…Figure 3 The most used plant species in the studies communities in both VF-CWs and HF-CWs; (Salgado et al, 2018) study in Cuba focused on domestic wastewater treatment by constructed wetlands enhanced with bioremediating rhizobacteria; (Lai et al, 2021) looked at the microbial community in a CW integrated with a moving bed bioreactor (MBBR) in China; (S. qing Wu et al, 2013) also looked at the microorganism community of an integrated vertical-flow constructed wetland; Finally, (Zeng et al, 2021) study looked into the microbial community that promotes COD, TP, and TN removal in CWs. The study by Salgado et al (2018) concluded that rhizospheric bacteria contain detoxifying enzymes that allow them to cope with polluted environments. The role of bacteria is clearly outlined by (S. qing Wu et al, 2013); the study indicated that facultative or obligatory aerobic/ anaerobic bacteria control the biodegradation of organic materials while aerobic respiration is more effective and feasible for the removal of organic contaminants.…”
Section: Application Of Cwsmentioning
confidence: 99%
“…These genera range of organic compounds. Pseudomonas is a well-known genus f ganic pollutants' removal and is commonly present in CWs [67], e.g. ics and the anticonvulsant carbamazepine [55,68,69].…”
Section: Microbial Compositionmentioning
confidence: 99%
“…These genera can remove a broad range of organic compounds. Pseudomonas is a well-known genus for organic and inorganic pollutants' removal and is commonly present in CWs [67], e.g., herbicides, antibiotics and the anticonvulsant carbamazepine [55,68,69]. Amaricoccus, similar to methylotrophs (in this case, Methylotenera), is a genus that uses organic compounds as a carbon source [70].…”
Section: Microbial Compositionmentioning
confidence: 99%